The Influence of Work Discipline and Motivation on the Performance of PPIC Employees at PT Adis Dimension Footwear in Tangerang Regency - Hudzaifi L, Berlian; Yulandari, Sri; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine: (1) the partial effect of work discipline on employee performance; (2) the partial effect of motivation on employee performance; (3) the simultaneous effect of work discipline and motivation on employee performance.This study employed a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all production employees at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 98 respondents, and the sampling technique used was simple random sampling. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis with SPSS 26.The results of this study indicate that (1) partially, work discipline significantly influences the performance of PPIC employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t-value > t-table (5.723 > 1.985) and a significance value of 0.000, which is less than the 0.05 value. Thus, Ha is accepted and H0 is rejected. (2) Partially, motivation significantly influences the performance of PPIC employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t value> t table (2.900>1.985) and a significance value of 0.000 smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, work discipline and motivation significantly influence the performance of PPIC employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated F> F table (75.405>3.09) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of work discipline and motivation, both partially and simultaneously, have a significant influence on the performance of PPIC employees at PT. Adis Dimension Footwear Balaraja-Tangerang.